Neurilemoma of Seminal Vesicle: A Case Report: Neurilemmoma of the Seminal Vesicle - Chaokamin, Isaris; Anukoolphaiboon, Apiwich; Chalieopanyarwong, Virote; Attawettayanon, Worapat; Khanungwanitkul, Kanin; Cattapan, Kamonwon; Thongsuksai, Paramee (PSU Medical Journal, 2021)
Neurilemmoma of the seminal vesicle is an extremely rare tumor. We report a neurilemmoma of right seminal vesicle. A 67-year-old man presented with moderate lower urinary tract symptoms. A magnetic resonance imaging of prostate performed due to high level of prostate specific antigen revealed a 8.1x8.1x7.1 cm, arising from right seminal vesicle. Laparoscopic resection of tumor was performed. The histopathology showed neurilemmoma arising from seminal vesicle.